1973
DOI: 10.1111/j.1748-1716.1973.tb05465.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Exocytosis of Storage Granules during Antigen‐Induced Histamine Release from Sensitized Rat Mast Cells in vitro An electron microscopic study

Abstract: ANDERSON, P., S. A. SLORACH and B. UVNXS. Sequential exocytosis of storage granules during antigen-induced histamine release from sensitized rat mast cells in vitro. Acta physiol. scand. 1973. 88. 359-372.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
46
1

Year Published

1976
1976
1994
1994

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 16 publications
5
46
1
Order By: Relevance
“…Early in the secretory process, single granules fuse with the plasma membrane, whereas at later stages membranes of adjacent granules in the cell interior fuse in succession to produce deep invaginations in the cell surface (1,19,28). These morphological observations correlate well with chemical measurements of release showing that 40-80% of the total cell histamine is secreted within 2 min (3,28).…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Early in the secretory process, single granules fuse with the plasma membrane, whereas at later stages membranes of adjacent granules in the cell interior fuse in succession to produce deep invaginations in the cell surface (1,19,28). These morphological observations correlate well with chemical measurements of release showing that 40-80% of the total cell histamine is secreted within 2 min (3,28).…”
supporting
confidence: 71%
“…This suggests that the first contact between the plasma and granule membranes is small and focal . Previous thin section studies of glutaraldehyde-fixed mast cells have on occasion demonstrated such localized contacts (1,4,20,28) .…”
Section: Discussionmentioning
confidence: 99%
“…Compound exocytosis seems to be the major mechanism of secretion in mast cells stimulated either with compound 48/80 (Rohlich et al, 1971), bee venom (Bloom and Haegermark, 1967), or with antigens in sensitized cells (Anderson et al, 1973). Also, compound exocytosis seems to occur in human platelets (Morgenstern et al, 1987) and neutrophils (Chandler et al, 1983;Chandler and Kazilek, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…This process was repeated, resulting in a series of inter connected cavities, and thus directly communicating with the extracellular space. Anderson et al (18) using TEM observed that sequential exocytosis of histamine-storing granules takes place when sensitized rat peritoneal mast cells are incubated with antigen. Tizard and Holmes (19) studied degranulation of rat peritoneal mast cells by SEM following chemical treatment and exposure to a specific antigen.…”
Section: Discussionmentioning
confidence: 99%